Exogenous normal lymph reduces liver injury induced by lipopolysaccharides in rats - Zhao,Z.G. (2014)
The liver is one of the target organs damaged by septic shock, wherein the spread of endotoxins begins. This study aimed to investigate the effects of exogenous normal lymph (ENL) on lipopolysaccharide (LPS)-induced liver injury in rats. Male Wistar rats were randomly divided into sham, LPS, and LPS+ENL groups. LPS (15 mg/kg) was administered intravenously via the left jugular vein to the LPS and LPS+ENL groups. At 15 min after the LPS injection, saline or ENL without cell components (5 mL/kg) was administered to the LPS and LPS+ENL groups, respectively, at a rate of 0.5 mL/min. Hepatocellular injury indices and hepatic histomorphology, as well as levels of P-selectin, intercellular adhesion molecule 1 (ICAM-1), myeloperoxidase (MPO), and Na+-K+-ATPase, were assessed in hepatic tissues. Liver tissue damage occurred after LPS injection. All levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in plasma as well as the wet/dry weight ratio of hepatic tissue in plasma increased. Similarly, P-selectin, ICAM-1, and MPO levels in hepatic tissues were elevated, whereas Na+-K+-ATPase activity in hepatocytes decreased. ENL treatment lessened hepatic tissue damage and decreased levels of AST, ALT, ICAM-1, and MPO. Meanwhile, the treatment increased the activity of Na+-K+-ATPase. These results indicated that ENL could alleviate LPS-induced liver injury, thereby suggesting an alternative therapeutic strategy for the treatment of liver injury accompanied by severe infection or sepsis.